EFFECTS OF UMRAH SERVICE QUALITY ON PILGRIMS’ SATISFACTION AMONGST UMRAH TRAVEL AGENTS IN SELANGOR, MALAYSIA - Mohd Nor, Mohd Adib Izzat; Mahdzar, Mazlina; Amil, Nur Hayati; Ikmal Hisam, Nur Khaleqa Izzah (Jurnal 'Ulwan, 2023)
This paper aims to learn about perceptions of service quality rendered by Umrah travel agents on pilgrims' satisfaction. The necessary data were gathered using a convenience sampling method based on self-administered structure questionnaires to complete this task. To fulfil the paper's sole purpose, 397 respondents' responses were collected via an online survey, analysed and used for this study. Regression results indicate that there is a relationship between service quality and pilgrims' satisfaction. Out of the five dimensions of service quality, three dimensions which are reliability, empathy, and responsiveness have a significant relationship with pilgrims' satisfaction with travel agencies. This study provides implications and justifications for travel agencies to consider service quality as a principle and a significant factor in building customer satisfaction and loyalty with travel agents.